Architectural changes in the regional lymph nodes of oral squamous cell carcinoma - Acharya, Swetha (J Oral Maxillofac Pathol, 2019)
BACKGROUND: The lymph nodes (LNs) in oral squamous cell carcinoma (OSCC) are enlarged as a result of reactive lymphadenopathy, metastasis or both. In response to tumor-associated antigens, diverse cell populations of LNs react in different ways, giving rise to a multitude of morphological patterns (MPs). The prognostic value of MPs has been contested. Hence, the aim of the study was to evaluate morphological alterations in the LNs related to LN metastasis (LNM), tumor size, grade and stage and the prognostic value for OSCC. MATERIALS AND METHODS: LN sections of 40 OSCCs were evaluated. Six MPs were observed: germinal center predominance (GCP), lymphocyte predominance (LP), sinus histiocytosis (SH), vascular transformation of sinuses (VTS), lymphocyte depleted (LD) and granulomatous reaction (GR). The data were subjected to Chi-square test. RESULTS: Four-hundred and eighteen nodes were evaluated, of which 24 were metastatic and 394 nonmetastatic. The predominant MP of LN reactivity was of VTS (116 nodes) followed by GCP (105); LP (90), LD (52), SH (43) and GR (12). A significant association was noted between LN status and the MPs. Risk of LNM with LP was less (13%) when compared with GCP (79%). A statistically significant relation was noted between the predominant MP and metastatic and nonmetastatic cases and with the tumor stage. CONCLUSION: GCP pattern prevails in metastatic and advanced-stage tumors. LP or VTS/SH is prominent in early-stage tumors and nonmetastatic cases. MPs indicate the immune status and aid in foreseeing susceptibility to LNM, thus serving as a surrogate marker.